Military veterans’ perspectives on using music to manage chronic pain: themes from the feasibility and acceptability of music imagery and listening interventions for analgesia study - Story, Kristin Maya; Wasmuth, Sally; Belkiewitz, Johanne M.; Whalen, Claire; Robb, Sheri L.; Bravata, Dawn M.; Bair, Matthew J. (Frontiers in Neurology, 2025)
IntroductionChronic pain conditions are common in military veterans, often leading to disability, psychological distress and high healthcare utilization. An interdisciplinary approach, informed by a biopsychosocial model, is recommended for patients with chronic pain. Music-based interventions have shown improvements in patients with pain, but results are inconsistent and most studies have concentrated on acute pain and in-person delivery.ObjectiveThe Feasibility and Acceptability of Music and Imagery for Analgesia (FAMILIA) explored the use of two telehealth delivered music interventions for chronic pain. As part of FAMILIA we conducted interviews to assess the veteran experience and acceptability of the music interventions.MethodsSemi-structured interviews were conducted with veterans who participated in either self-directed, independent music listening or a therapist-delivered music and imagery intervention in a three-arm randomized controlled trial. All interventions were conducted by board certified music therapists over a HIPAA approved telehealth platform. Interviews were conducted by team members who did not deliver the intervention and included questions about the intervention(s), delivery format, barriers and facilitators to study participation.ResultsSixteen interviews were recorded, transcribed, and deidentified for analysis. The research team identified ten themes, drawn from the veterans’ experiences from pre to post intervention about the acceptability, motivation for joining, challenges, and perceived benefits of the telehealth-delivered music interventions.ConclusionVeteran patients found FAMILIA acceptable and endorsed using music listening or music and imagery as a non-pharmacological support for management of chronic pain and accompanying psychological symptoms.Clinical trial registrationClinicaltrial.gov, Identifier NCT05426941.